Tissue Inhibitor of Metalloproteinase-1 Is Confined to Tumor-Associated Myofibroblasts and Is Increased With Progression in Gastric Adenocarcinoma. (August 2016) - Alpízar-Alpízar, Warner; Laerum, Ole Didrik; Christensen, Ib J.; Ovrebo, Kjell; Skarstein, Arne; Høyer-Hansen, Gunilla; Ploug, Michael; Illemann, Martin
The tissue inhibitor of metalloproteinase-1 (TIMP-1) inhibits the extracellular matrix–degrading activity of several matrix metalloproteinases, thereby regulating cancer cell invasion and metastasis. Studies describing the expression pattern and cellular localization of TIMP-1 in gastric cancer are, however, highly discordant. We addressed these inconsistencies by performing immunohistochemistry and in situ hybridization analyses in a set of 49 gastric cancer lesions to reexamine the TIMP-1 localization. In addition, we correlated these findings to clinicopathological parameters. We show that strong expression of TIMP-1 protein and mRNA was observed in a subpopulation of stromal fibroblast-like cells at the periphery of the cancer lesions. In a few cases, a small fraction of cancer cells showed weak expression of TIMP-1 protein and mRNA. The stromal TIMP-1-expressing cells were mainly tumor-associated myofibroblasts. In the normal-appearing mucosa, scattered TIMP-1 protein was only found in chromogranin A positive cells. TIMP-1-positive myofibroblasts at the invasive front of the tumors were more frequently seen in intestinal than in diffuse histological subtype cases ( p =0.009). A significant trend to a higher number of cases showing TIMP-1 staining in myofibroblasts with increasing tumor, node, metastasis (TNM) stage was also revealed ( p =0.041). In conclusion, tumor-associated myofibroblasts are the main source of increased TIMP-1 expression in gastric cancer.